Post-Weaning Feed Intake and Performance of Bulls Developed in an Automated Feed Intake Management System - J. Wyatt L. Banks; Karol E. Fike; Jason M. Warner (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:Our objectives were to compare expected and observed dry matter intake (DMI) and average daily gain (ADG) using modeled nutrient requirement equations, and to evaluate change in DMI over time of beef bull calves fed in an automated feed intake system. Study Description:Feed intake and performance data from purebred Angus, Hereford, and Simmental bull calves across two calf crops [birth years 2021 (n = 40) and 2022 (n = 37)] were utilized for this analysis. Projected DMI and ADG were calculated for each group of bulls by year on an individual basis using the Growing Bull module of the Excel-based Beef Ration and Nutrition Decision Software (BRANDS) formulation program (Iowa State University, Ames, IA). These predicted figures were compared to the Insentec intake data and analyzed via SAS. Results:In 2021–2022, a strong positive correlation (r= 0.78,P<0.01) was observed between actual and predicted DMI. There was a highly correlated (r= 0.84,P<0.01) relationship for the observed and predicted DMI for 2022–2023 as well. Actual ADG for both years was markedly higher than predicted. This result supports that BRANDS more accurately predicts DMI compared to ADG, and that substantial individual intake variation exists. The Bottom Line:DMI increases over time as days of test period increase for growing bulls in an individually fed intake system, and though significant day-to-day variation exists, the BRANDS program appears to more accurately predict DMI than ADG.
Keywords: bulls; feed intake; performance